Mitsubishi Electric / Muhammad Rais Helmi Md Aris - Md Aris, Muhammad Rais Helmi (2022)
This case study assignment is about analyzing the chosen product. The company that has been chosen by me is Mitsubishi Electrical. From the various choice of products they provided, I have chosen the air condtioner technology. In this case study, I manage to finish the SWOT analysis about the product that I have chosen which contains the strength, weakness, opportunity, and threat of the air conditioner. The main problem for this product is that the website specifically for air conditioner is outdated or old unlike the refrigerator or electric fan, the others two products provided by Mitsubishi Electrical. For the problem, I have come up with the solution which is to upgrade the website for the air condtioner so it will on pair with the rest of the others product.